Changes in microbial pathogen dynamics during vermicomposting mixture of cow manureâorganic solid waste and cow manureâ sewage sludge - Hossein Karimi; Mehdi Mokhtari; Faezeh Salehi; Sajed Sojoudi; Aliasghar Ebrahimi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Microbial pathogens can lead to health problems and disease transmission. Present study aimed to evaluate the microbial quality and quantity of vermicompost production and to compare to the current Iranian standards to protect public health and environmental concerns. Method This is a pilot-scale experimental study conducted in the Public Health laboratory of Shahid Sadoughi University of Medical Sciences. The samples included organic municipal solid waste, cow manure and wastewater treatment plant sludge which are used for vermicompost production. The samples are mixed as cow manureâorganic waste and cow manureâsewage sludge in two reactors. Microbial tests such as fecal coliforms (FC) and parasite egg (Ascaris) were carried out during start, processing and curing time with duplication analysis in 56 days. Totally, a number of 128 samples was analyzed. Analyses were conducted according to standard methods. Data analysis was conducted through one-way ANOVA and Duncan tests. Results The results showed a significant reduction in number of FCs in cow manureâorganic waste so that the number of 350,000 MPN/g in the raw sample decreased to 800 MPN/g within 8-week period, also FC in the case of cow manureâsewage sludge was achieved to 2400 from 6,500,000 MPN/g. In two cocomposting cases, the parasite eggs were completely removed in the second week. Conclusion The results showed vermicomposting as a feasible method to convert waste into fertilizer humus in agriculture which also enables to achieve Iranian class A compost standard.